2019
DOI: 10.1093/gastro/goz045
|View full text |Cite
|
Sign up to set email alerts
|

Volvulus of the ileal pouch–anal anastomosis: a meta-narrative systematic review of frequency, diagnosis, and treatment outcomes

Abstract: Background Proctocolectomy with ileal pouch–anal anastomosis (IPAA) is the surgical procedure of choice for medically refractory ulcerative colitis and familial adenomatous polyposis. While rare, a pouch volvulus can occur. We aimed to determine the frequency, presentation, and management approach of pouch volvulus in patients with IPAA. Methods A systematic search of published literature was performed by a medical reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…14 We kept items focused on the representativeness of the cases and ascertainment of outcome and removed items that related to the selection of the controls and comparability. This tool has been applied in many previous publications, 3,[15][16][17][18] with good consistency among reviewers. The assessment of methodologic quality for the 10 included cohorts and the overall risk of bias for these cohorts are found in Supplemental Information.…”
Section: Assessment Of Methodologic Qualitymentioning
confidence: 99%
“…14 We kept items focused on the representativeness of the cases and ascertainment of outcome and removed items that related to the selection of the controls and comparability. This tool has been applied in many previous publications, 3,[15][16][17][18] with good consistency among reviewers. The assessment of methodologic quality for the 10 included cohorts and the overall risk of bias for these cohorts are found in Supplemental Information.…”
Section: Assessment Of Methodologic Qualitymentioning
confidence: 99%
“…Repeated symptoms were also observed in this case, and he was referred to our hospital for the purpose of surgery. Enema and MDCT are useful in the diagnosis of a volvulus, and corkscrew and whirl signs are typical findings [1,2]. The previous reports showed that the risk factors of pouch volvulus were minimally invasive technique, few adhesions in the pelvis, female sex, low BMI, the oral intestinal tract reaches the pelvis with sufficient margins and an anterior positioning of the pouch mesentery [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…The common site of a pouch volvulus is reported to be the pouch–anal anastomosis and the middle of the pouch [ 1 9 ]. In this case, the afferent limb of the pouch had a long-axis rotated volvulus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations